Simultaneous measurement of transverse load and temperature using hybrid structured fiber-optic Fabry–Perot interferometer - Wu, Yongfeng (Sci Rep, 2017)
We experimentally demonstrated a novel fiber-optic hybrid structured Fabry–Perot interferometer with special air-cavity for simultaneous measurement of transverse load and temperature. By the linear phase finite impulse response filters, the transverse load sensitivities of the air-cavity and the silica-cavity are 1272.71 pm/N and −53.07 pm/N, respectively, and temperature sensitivities of the air-cavity and silica-cavity are 1.1 pm/°C and 14 pm/°C. Thus, the different sensitivities of silica-cavity and air-cavity to transverse load and temperature indicate that such a structure can be used to simultaneously measure transverse load and temperature.